The Facebook Groups and Pages of Malagasy Migrants in France: Hubs of Peer-to-Peer and Spontaneous Solidarity - Fortunat Miarintsoa Andrianimanana (MDPI AG, 2021)
How do social platforms such as Facebook help migrant communities cope with the adversities faced during the migration journey? This is the question that drove this study, which explores the on- and offline experiences of Malagasy migrants in France during their migration journeys. We use complementary mixed methods, including an online survey (2021, n = 340) and participant observation of in-group and public interactions on 28 Facebook groups and pages of this community. We found that peer-to-peer solidarity as a collective response to the adversities faced during migration is present and very active within the Malagasy community in France. The exchanges among the members of this community concerning matters such as administrative issues and the transport of parcels between France and Madagascar are intense and continuous. Beyond this, solidarity chains are temporarily activated in response to specific needs, and particularly in collectively challenging times such as the COVID-19 pandemic. Our research also found that in their groups and pages, the Malagasy in France engage less frequently in other vital issues, such as finding work.